Faustian bargaining in a regime complex: IMF-RFA cooperation in Europe (2008-2012) - Iaydjiev, I (2018)
What explains IMF behavior in Europe between 2008 and 2012? Harshly criticized in Greece, yet tentatively praised in Hungary, the institution found itself playing different roles as it responded to a string of financial crises. Its programs varied substantially in terms of conditionality, financing, and private sector involvement. This thesis explores why, highlighting the changing global financial safety net, which is both expanding and becoming more decentralized due to the spectacular rise of regional financing arrangements (RFAs). Existing theories of IMF behavior assume the Fund to be a stand-alone institution and analyse financial assistance as the outcome from the interplay between creditors, borrowers, and staff. By focusing on dynamics within the IMF, however, they miss how developments outside the institution are increasingly shaping its behavior. This thesis brings in the role of changes in the institutional environment by drawing on the literature on regime complexity. The proliferation of RFAs alters the outside options of all actors, which affects their bargaining power. This opens the way for new strategies, through which creditors can entangle institutions by creating overlaps, borrowers can engage in confrontation between alternative financing institutions, and the IMF can find means to co-work with RFAs. These in turn affect whose preferences shape program design. This argument is tested empirically through process-tracing and comparing three cases of IMF-RFA cooperation in Europe. In Hungary, the IMF led the way in shaping a surprisingly 'generous' program with little constraint from the EU. However, in Latvia, the Fund found itself a 'junior partner' in a program driven by local authorities with the support of an European RFA. In Greece, the interests of creditors were paramount, securing IMF acquiescence through the threat of exclusion. These findings point to significant challenges for the Fund going forward. As RFAs continue to proliferate around the world, the IMF needs to avoid the temptation of striking even more Faustian bargains that keep it at the table of financial assistance at the cost of becoming a junior partner.